Outward Foreign Direct Investment from China: Recent Trend and Development. Issue 5 (3rd September 2017) - Wang, Yanting; Zhao, Lin
Abstract : Along with the economy transition and industry upgrading in China, the outward foreign direct investment (OFDI) activities by Chinese enterprises have been steadily increasing during recent years. This study investigates the current status and the underlying motivations for Chinese firms to enter foreign markets. We discuss relevant economic policies that drive the recent trend of OFDI from China. The efforts by the Chinese government to promote innovations and cross-border economic collaboration paved the way for more OFDI opportunities in the future.